ETHNOBOTANICAL USES OF MEDICINAL PLANTS: A REVIEW: Life Science-Ethono Botany - MEGHENDRA SHARMA; ASHWANI KUMAR (International Journal of Life Science and Pharma Research, 2013)
Ethnobotany is a distinct branch of natural science dealing with various aspects such as anthropology, archaeology, botany, ecology, economics, medicine, religious, cultural and several other disciplines. Ethnobotany is usually defined as anthropological approach to botany. There are several methods of ethnobotanical research and those relevant to medicinal plants are archaeological search in literature, herbaria and the field studies. Recently ethno-botanical studies have gained importance during recent years. In the present paper ethnobotanical studies have been conducted on some plants of Rajasthan